2019
DOI: 10.3390/insects10040101
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Sterilization Dose of Adult Males in Asian Tiger Mosquito Pupae

Abstract: The pathogen-carrying tiger mosquito, Aedes albopictus, has spread from the Western Pacific and Southeast Asia to Europe, Africa, the Middle East, North and South America, and the Caribbean. This species of mosquito transmits arboviral infections, such as yellow fever, chikungunya, dengue, zika, and several encephalitides. The objective of this research was to provide a radiation dose inducing sterilization in adult male Ae. albopictus in the pupal stage. A cobalt-60 source of gamma radiation at a dose rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Differences in the age of irradiated adults: according to Welsh et al [26], both genders used in their trials were not more than 24 h old, while we irradiated slightly older males. In studies with Aedes albopictus , it has been demonstrated that mosquito pupae irradiated at different ages show differences in terms of sterility rates [47]. Consequently, we can consider that the differences in adult age are a possible reason for the decrease of sterility in Experiment 1, compared to the values reported in Welsh et al [26].…”
Section: Discussionmentioning
confidence: 75%
“…Differences in the age of irradiated adults: according to Welsh et al [26], both genders used in their trials were not more than 24 h old, while we irradiated slightly older males. In studies with Aedes albopictus , it has been demonstrated that mosquito pupae irradiated at different ages show differences in terms of sterility rates [47]. Consequently, we can consider that the differences in adult age are a possible reason for the decrease of sterility in Experiment 1, compared to the values reported in Welsh et al [26].…”
Section: Discussionmentioning
confidence: 75%
“…It appears that the last nymphal stage and newly moulted virgin BMSB are more radiosensitive than older new season virgin and overwintered male BMSB. Age of the same developmental stage also should be taken into consideration, Machi et al (2019) indicated that Aedes albopictus mosquito pupae irradiated at different ages showed differences in the level of their sterility rates [33]. Our nymphs used here took 1-14 days to develop into adults post-irradiation, which may have had an effect on their radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Exposing insects to sterilizing doses of irradiation can impact their longevity and mating competitiveness ( Lance et al, 2000 ). Sometimes the lethal dose of radiation is sufficiently close to the sterilizing dose of radiation such that achieving 100% sterilization means that the vast majority of the males will not survive ( Ricardo Machi et al, 2019 ). Many batch irradiation approaches do not separate males from females prior to release, and this can both decrease the effectiveness ( Rendón et al, 2004 ), and lead to public health concerns when the female insect is a disease vector ( Benedict, 2021 ).…”
Section: Introductionmentioning
confidence: 99%